A method for spatio-temporal process assessment of eco-geological environmental security in mining areas using catastrophe theory and projection pursuit model. (October 2021) - Shao, Huaiyong; Sun, Xiaofei; Lin, Ying; Xian, Wei; Zhou, Yingzhi; Yuan, Linguo; Qi, Jiaguo
It is a universal problem that the eco-geological environment has been damaged by mineral resources exploitation. The accurate evaluation of eco-geological environmental security (EES) in mining areas is essential for restoring the environment of the mining area. However, a robust approach to obtaining an accurate evaluation of ESS has not yet been produced due to the complex spatio-temporal process of EES. Here, we developed a new method for enabling the quantitative evaluation of the EES spatio-temporal process. The EES evaluation index system of mining areas was established from both natural and anthropogenic aspects. The EES evaluation method was developed by combining the catastrophe theory and projection pursuit model (PPM). Then, with the support of remote sensing (RS) and a geographic information system (GIS), the method was applied to evaluate the spatio-temporal process of EES in Panxi mining area. The bifurcation curve and receiver operating characteristic curve were used to verify the developed method. The results showed that this method could accurately evaluate the spatio-temporal process of EES in a mining area and could successfully recognise the threshold value to distinguish the safe status and unsafe status. Strong spatio-temporal variations of EES in Panxi area were found, which may be the result of the combined effect of multiple factors (e.g. mineral resource exploitation, soil erosion, and ecological restoration). In summary, the combination of catastrophe theory and PPM with RS and GIS to quantitatively evaluate the spatio-temporal process of EES in mining areas is a robust method.